Pemberdayaan masyarakat melalui pembuatan eco-enzyme dari sampah organik sebagai cairan multifungsi bagi masyarakat Desa Batu Belah, Kecamatan Kampar - Chairul Chairul; Silvia Reni Yenti; Evelyn Evelyn; Maria Peratenta Sembiring; Yusnimar Yusnimar; Komalasari Komalasari; Desi Heltina; M. Iwan Fermi; Deviona Deviona; Alhabsy Affif; Annisa Ulhasanah; Aqilla Cahyani; Fitri Zulva Hasanah; Hasby Herdinasrul; Nurul Azizah; Misrulina Misrulina; Rahmi Adisti; Rizaldi Saputra; Sherly Fitri Rahmadhani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The Community Service Team of the Faculty of Engineering of Riau University together with students of the Riau University 2022 Kukerta team in Batu Belah Village, Kampar District provided assistance and demonstrations on how to make eco-enzyme solution from organic waste as a multifunctional solution. The eco-enzyme solution is a liquid resulting from the fermentation of organic waste in the form of fruit and vegetable waste which is added brown sugar and water in a ratio of 3:1:10 for 90 days. The purpose of this community service activity was to provide knowledge to the community and housewives group of Batu Belah Village, Kampar District to utilize organic waste into eco-enzyme solution and the benefits of eco-enzyme for various functions. In the implementation of community service activities, several stages were carried out including the stage of meeting with village officials and recording enthusiasts who wanted to take part in the training, then from the results of the participant data, the socialization stage and demonstration of training materials for making eco-enzyme solutions. The last stage to see the achievement of the training results is monitoring the level of understanding and enthusiasm of the participants. The results of the service showed that the Batu Belah Village community was very enthusiastic about participating in the socialization of making eco-enzyme from organic waste and was willing to practice it in their respective homes with an understanding level of 93.3%.